Aplicación de un procedimiento para el control de gestión en la Cooperativa de Ahorro y Crédito Chone LTDA. - Cedeño Andrade, Tania Gema (2020)
The objective of this research was to know the performance of the management control of the Cooperative, this was carried out in the savings and credit Cooperative Chone Ltda. in Chone, in the first stage of the object of study the interview was preceded to the manager and the employee survey to obtain information on the operation of the management control and determine the deficiencies found using the Ishikawa diagram tool. In the second stage, the bibliographicreview of the research was carried out to select and implement the management model, selecting the Balanced scorecard because it allows senior management to monitor organizational performance from four different perspectives; financial perspective (profitability and sales growth index), customer perspectives (number of partners, degree of satisfaction), process perspective (innovation in the production of services, after-sales services), and leaming and growth perspective (permanence of employee, amount allocated for leaming and growth). By preparing the command board, the Cooperatives strategic objectives can be known, allowing the execution of the traffic light that mediates the fulfillment of the planned mints, resulting in the fact that the goals are not being met in three indicators; growth in services, degree of satisfaction, amount allocated for learning and growth. With the elaboration of the balanced scorecard, it was possible to know the current state of the Cooperative’s management control, allowing the development of new strategies using the 5W+1H tool.